INISIASI MENYUSUI DINI - Nurhaida Br Kaban (Universitas Negeri Medan, 2017)
The purpose of this study was to determine the level of knowledge of primigravida pregnant women about early breastfeeding initiation at the Sundari General Hospital Medan. The research design used is descriptive. The sample technique used is probability simple random sampling with the number of samples is 65 people. Data were obtained by using questionnaires that were distributed and filled directly by the respondents. The data analysis used is univariate analysis that is to know systematically picture of pregnant primigravida mother about Initiation of Early Breastfeeding at Sundari General Hospital Medan. The results showed that most of primigravida mother's knowledge about early initiation of breastfeeding was less that of 42 people (64,6%) and small knowledge of primigravida mother about early initiation of breastfeeding is 10 people (15,4%). It is advisable to health agencies should as often as possible to counseling related to mother and child health, especially about the importance of early breastfeeding initiation to pregnant women in order to improve the knowledge of pregnant women about the benefits of early breastfeeding initiation.